Efficacy of Self-Compassion Training on the Perceived Stress and Psychological Coherence in Elderly Caregivers - Fatemeh Masoudi; Atefeh Nezhadmohamad Nameghi; Parvane Ghodsi (Hamadan University of Medical Sciences, 2024)
Background and Objective: The present study was conducted to investigate the efficacy of self-compassion training on perceived stress and psychological coherence in elderly caregivers. Materials and Methods: This research was a quasi-experimental study with pretest-posttest and control group design and two-month follow-up period. The statistical population of the present study was consisted of elderly caregivers of centers under the supervision of the Ministry of Health, in Tehran, Iran, in 2022. A total of 27 elderly caregiver were selected through available sampling method and randomly assigned into Intervention and control groups. The experimental group received ten sessions of self-compassion training during two-and-a-half-months. The applied questionnaires in this study included Perceived Stress Scale (Cohen, Kamarck, T, Mermelstein, 1983) and Psychological Sense of Coherence Questionnaire (Flensborg, Ventegodt, Merrick, 2006). The collected data were analyzed using mixed ANOVA in SPSS software (version 23). Results: The obtained results showed that self-compassion training significantly affects the perceived stress (P<0001; Eta=0.61; F=39.69) and psychological coherence (P<0001; Eta=0.63; F=43.25) in elderly caregivers. Conclusion: According to the findings of the study, it can be concluded that self-compassion training can be used as an efficient method to decrease the perceived stress and increase psychological coherence in elderly caregivers.